Sistem Pengurusan Visa Kru Kapal pada Perusahaan PT. Seantero Tiram Samudra - Galuh Farras Arie; Nuraini Purwandari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Numerous individuals use the services of a company to manage their visas. PT. SEANTERO TIRAM SAMUDRA is an organization that provides visa management services. PT SEANTERO TIRAM SAMUDRA is included in the group of businesses that are still manually recording reports. PT SEANTERO TIRAM SAMUDRA is constrained by the fact that daily reports are only stored in a ledger's daily journal, and the data can be damaged or lost. This study's objective is to design a desktop-based visa management information system that provides an information system to support business processes, particularly in the company's data storage division. The research method employed is the method of developing a prototype system with UML (Unified Modeling Language) system modeling; the outcome of the research is a system that can process, store, and report data. Based on the results of the testing, a desktop-based system has been developed, which can be operated according to the company's needs.